The Comparison Between Platelet Count and Hematocrit Levels in Primary and Secondary Dengue Hemorrhagic Fever Infection: Platelet Count and Hematocrit Levels - Jennifer Oscar; Freddy Ciptono (STIKes Mandala Waluya Kendari, 2023)
Background: Dengue hemorrhagic fever is an infectious ailment that exhibits a significantly elevated incidence rate in Indonesia. Dengue hemorrhagic fever can be classified into primary and secondary infection, where the secondary infection tends to cause more severe clinical manifestations. Hematocrit and platelet count are essential parameters observed in dengue hemorrhagic fever. This study aimed to analysed the existence of statistically significant differences in the level of hematocrit and platelet count between primary and secondary dengue hemorrhagic fever infections. Methods: This study applied analytical observational cohort design with 60 samples in the form of medical record and laboratory data of hematocrit level and platelet count from patients diagnosed with dengue hemorrhagic fever. Results: The results reveal significant differences in hematocrit and platelet values between primary and secondary DHF infection. Hematocrit value arises 2.73% higher (p = 0.043) and the platelet count drops 50,500/μl lower (p = 0.00) in secondary dengue hemorrhagic fever infection. Conclusions: Significant differences of hematocrit and platelet values were found between primary and secondary dengue hemorrhagic infection. Clinicians should increase wary of secondary dengue hemorrhagic fever infected patients due to more severe clinical manifestations.